2021
DOI: 10.3390/ijerph18115626
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Measures and Strategies for a Healthy and Sustainable Extended Working Life and Employability—A Deductive Content Analysis with Data Including Employees, First Line Managers, Trade Union Representatives and HR-Practitioners

Abstract: Due to the global demographic change many more people will need to work until an older age, and organisations and enterprises need to implement measures to facilitate an extended working life. The aim of this study was to investigate organisational measures and suggestions to promote and make improvements for a healthy and sustainable working life for all ages in an extended working life. This is a qualitative study, and the data were collected through both focus group interviews and individual interviews that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(104 citation statements)
references
References 30 publications
(74 reference statements)
5
99
0
Order By: Relevance
“…There are some areas that determine whether individuals can versus want to work respectively. Furthermore, these determinant areas are important to the individual's retirement and retirement planning [1,2,[14][15][16]19]. In an organisation or enterprise, it is mainly the manager who makes decisions regarding these determinant areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some areas that determine whether individuals can versus want to work respectively. Furthermore, these determinant areas are important to the individual's retirement and retirement planning [1,2,[14][15][16]19]. In an organisation or enterprise, it is mainly the manager who makes decisions regarding these determinant areas.…”
Section: Discussionmentioning
confidence: 99%
“…Retirement is a valid and socially acceptable way for an employee to withdraw from working life, e.g., from a physically and mentally demanding work situation, depending on whether their personal financial situation will be sufficient with a pension, whether they do not want to continue working due to the social situation and environment in the workplace, their skills not being utilized in the work tasks or that they do not experience motivation and stimulation in their work tasks [1,2]. However, the proportion of senior citizens is continuously increasing in most of the industrial world [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has identified some of the most relevant ones; thus, for example, for personal resources, perceived health (e.g., Brokerhof et al, 2020;Brouwers et al, 2015;Fleuren et al, 2018a;van Gorp et al, 2018) and vitality (e.g., van Holland et al, 2018). In the case of external resources, research has often included social support at work (e.g., Hansen et al, 2020;Koolhaas et al, 2015;Nilsson & Nilsson, 2021) and work organization factors (e.g., Houkes et al, 2020;Tonnon et al, 2017;van de Ven et al, 2014). However, sufficient consistency between studies is not appreciated, so it would be advisable to identify the most relevant ones grouped by dimensions.…”
Section: Individual Se and Contextual Sementioning
confidence: 99%
“…Thus, a life-course perspective with measures for a sustainable working life with possibilities for, for example, social participation, is important. A starting point for such a measure could be the theoretical swAge-model [65,66], focusing measurements on health effects associated with working environment, for personal financial security, for social inclusion and social support in the work situation, and for creativity and intrinsic work motivation [67]. A supportive work environment with an organization that encourage employees to participate in decision making, i.e., high control, are vital for a sustainable working life.…”
Section: Possible Implicationsmentioning
confidence: 99%